2014
DOI: 10.1016/j.bbalip.2013.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term biopermanence of ceramides, cholesteryl esters, and ether-linked triglycerides with very-long-chain PUFA in the cadmium-damaged testis

Abstract: Cadmium is known to harm rat testis by causing the dose-dependent apoptotic or necrotic death of seminiferous epithelium cells. Here we investigated how this affects the lipids with long-chain (C18-C22) and very-long-chain (C24-C32) polyunsaturated fatty acids (VLCPUFA) typical of spermatogenic and Sertoli cells. A severe acute inflammatory reaction resulted from the massive necrotic death of these cells two days after a single high (4 mg/kg) dose of CdCl2. This led to the conversion of most testicular glycero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Cadmium exposure is known to affect lipid metabolism even at low concentrations [3941] and to cause a dose dependent increase in plasma triglyceride levels [42]. Using Oil-Red-O staining, which is able to dye neutral triglycerides and glycolipids, we found that cadmium induced lipid droplet accumulation that was not observed when cells were co-treated with OLE and cadmium (Fig 8A).…”
Section: Resultsmentioning
confidence: 90%
“…Cadmium exposure is known to affect lipid metabolism even at low concentrations [3941] and to cause a dose dependent increase in plasma triglyceride levels [42]. Using Oil-Red-O staining, which is able to dye neutral triglycerides and glycolipids, we found that cadmium induced lipid droplet accumulation that was not observed when cells were co-treated with OLE and cadmium (Fig 8A).…”
Section: Resultsmentioning
confidence: 90%